Media Construction on the Closeness of Prabowo, Hary Tanoe, and Trump - Dedi Prasetyo; Made Wilantara (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: From the perspective of social construction theory and narrative authority, this framing reflects the tendency toward mediatized politics and a shift in authority from systemic institutions to individual figures. This study aims to analyze how the online news outlet Republik Merdeka Online (RMOL) frames the narrative of the close relationship between President Prabowo Subianto, businessman Hary Tanoesoedibjo, and former U.S. President Donald Trump, in the context of the 32 percent import tariff policy imposed by the United States on Indonesia on April 3, 2025. Methodology: This research employs a descriptive, qualitative approach, utilizing Robert Entman’s framing analysis model, which comprises four main elements: defining problems, diagnosing causes, making moral judgments, and suggesting remedies. Findings: The findings reveal that RMOL actively constructs a discourse that positions personal relationships among elites as an informal diplomatic instrument perceived as more effective than formal state mechanisms. RMOL’s framing emphasizes Prabowo as a strategic leader and Hary Tanoe as a bridge to Trump, while overlooking the role of state institutions and the voices of civil society. Furthermore, the use of visualization strategies and emotive diction reinforces symbolic construction and the personalization of power. Implications/Novel Contribution: This study recommends the importance of media literacy and balance in foreign political journalism and the need for a more inclusive discursive space for non-elite actors to foster a healthy and reflective information democracy.